Examining the Utility of Resective Epilepsy Surgery in Children With Electrical Status Epilepticus in Sleep: Long Term Clinical and Electrophysiological Outcomes - Marashly, Ahmad; Koop, Jennifer; Loman, Michelle; Lee, Yu-Wen; Lew, Sean M. (Frontiers in Neurology, 2020)
Background: Electrical Status Epilepticus in Sleep (ESES) is an epileptic encephalopathy syndrome characterized by infrequent clinical seizures and prominent interictal burden during slow wave sleep associated with cognitive deficits and behavioral dysfunction. Medical treatment with anti-epileptic drugs is often unsuccessful. Resective surgery may be a valuable option in carefully selected patients. This case series aims to describe the indications, long term results and utility of resective surgery for ESES. Methods: Information on fourteen patients who underwent surgery for epilepsy and ESES at the Children’s Hospital of Wisconsin between 2007 and 2017 is included. Clinical, electrographic and neuropsychological features and outcomes are described in detail. Results: The most common pathology was encephalomalacia due to perinatal middle cerebral artery stoke (5/14). Twelve patients had imaging findings of perinatal pathologies; however, 2 patients had normal magnetic resonance imaging. Surgery was performed to control refractory epilepsy in 8 patients. Six patients had no clinical seizures for 1-6 years prior to surgery, one of which had no known clinical seizures at all. All showed cognitive declines (6/14) or impairment (8/14) on neuropsychological assessments, and surgery was suggested to minimize further cognitive declines. The most common surgical procedure was lateral hemispherotomy (10/14). Temporo-parieto-occipital disconnection, frontal lobectomy, parieto-occipital resection and limited corticectomy were also used, with good outcomes for the first three procedures. Clinical follow up mean was 4.4 years and 12 patients had excellent seizure outcome. Electroencephalography (EEG) follow up mean was 3 years and ESES resolved in 12/14 patients. All patients completed post-surgical neuropsychological evaluation with mean follow-up of 17.46 months. Conclusions: Resective surgery is an effective treatment for selected cases of ESES, producing long term seizure freedom, resolution of ESES and stabilization of cognitive and behavioral functioning in most patients. Our case series is the largest single center cohort description addressing resective surgery for ESES. Outcomes in this sample suggest that good long-term seizure, EEG and cognitive/behavioral outcomes can be achieved in patients with normal brain imaging and in limited lobar or multi-lobar resections. Moreover, patients with ESES and very infrequent clinical seizures can benefit from surgery with stabilization of cognitive and behavioral functioning.